EFEKTIVITAS BERMAIN LEGO UNTUK MENGEMBANGKAN ASPEK SOSIAL EMOSIONAL ANAK USIA DINI - Ni Ketut Arsini; Serli Marlina (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Early childhood education plays a crucial role in supporting children's overall development, including their social development. This study aims to examine the effectiveness of LEGO games in improving the social skills of early childhood. The study employed a quantitative approach with a quasi-experimental method and a Pretest–Posttest Control Group Design. The study population comprised all 27 children at Hidara Kindergarten, divided into two classes: Class A1 as the experimental group with 13 children, and Class A2 as the control group with 14 children. Data were collected using observation sheets, and hypothesis testing employed the Paired-Sample T-test. Results revealed a significance value of 0.001 (< α 0.05), indicating a statistically significant difference between experimental and control classes. The mean posttest score of the experimental class was 87.69, compared to 76.43 for the control class, yielding a difference of 11.26 points. With an effect size of 0.67 (moderate category), the contribution reached 73%. It is concluded that playing LEGO effectively enhances social aspects among young children, especially cooperation, sharing, communication, emotional regulation, empathy, and confidence. LEGO proves not merely as entertainment but as a strategic instructional instrument capable of optimally stimulating children's interpersonal